2013
DOI: 10.1097/ta.0b013e318299d650
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital intubation success rates among Israel Defense Forces providers

Abstract: After the first ETI attempt, success with subsequent attempts tended to fall, with minimal improvement in overall ETI success seen after the third attempt. Because CRIC exhibited excellent success as a backup airway modality, we advocate controlling the airway with CRIC if ETI efforts have failed after two or three attempts. We recommend that providers reevaluate whether definitive airway control is truly necessary before each attempt to control the airway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…For example, it is known that a rapid sequential intubation of critical patients changes the results. A study in Germany determined the intubation success of paramedics as 46.4%, but the success rate is 99% in the USA 16 and 78% in Israel 17 . Manikin studies have showed variable results.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is known that a rapid sequential intubation of critical patients changes the results. A study in Germany determined the intubation success of paramedics as 46.4%, but the success rate is 99% in the USA 16 and 78% in Israel 17 . Manikin studies have showed variable results.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, moving forward to the next step is essential in preventing fixation error and entering a CICO scenario. Alternative airway methods or an ESA should be selected rapidly because after three failed attempts, the chance for successful tube placement is limited and does not warrant the risks and side effects of subsequent ETI attempts [20]. Strict adherence to guidelines, the use of a SAD (i.e., laryngeal masks) and the use of video laryngoscopes in our HEMS operation likely contributed to the low number of ETI attempts and ESAs.…”
Section: Discussionmentioning
confidence: 95%
“…This study has shown the feasibility of using the modified GP and GG technologies to instruct critical care physicians in ETI with the provision of excellent vocal cord visualization and accurate calculation of Cormack-Lehane scores. [14]. We have proposed an inexpensive yet effective system utilizing GP and modified GG technologies which can be used to teach ETI to learners of any level of medical expertise.…”
Section: Resultsmentioning
confidence: 99%